Synthetic aperture sonar for sub bottom imaging - Dutkiewicz, Marek Karol (Department of Electrical Engineering, 2016)
The major problems associated with implementing synthetic apertures in sonar may be overcome by applying the technique to sub-bottom imaging. The use of a low frequency aids both penetration of the sediment and the attainment of long coherent apertures. The implementation of synthetic apertures realises a narrow fan beam. By directing this beam out sideways, a more rapid survey rate is possible than that achieved by the normal echo-sounding mode used in sub-bottom profiling. The synthetic aperture technique appears to offer significant advantages over that of parametric arrays, for high resolution sub-bottom imaging. Synthetic apertures have been implemented in a laboratory tank, under controlled conditions at a fresh water reservoir, and under realistic operational conditions at sea. Encouraging results have been obtained.